Avoidance of urinary catheterization to minimize in-hospital complications after transcatheter aortic valve implantation: An observational study. (January 2018) - Lauck, Sandra B; Kwon, Jae-Yung; Wood, David A; Baumbusch, Jennifer; Norekvål, Tone M; Htun, Nay; Stephenson, Leo; Webb, John G
Background: Contemporary transcatheter aortic valve implantation (TAVI) devices and approach present opportunities to review historical practices initially informed by early treatment development and cardiac surgery. The avoidance of urinary catheterization in the older TAVI population is a strategy to minimize in-hospital complications. The purpose of the study was to explore elimination-related complications following the phased implementation of a default strategy of avoiding urinary catheterization in patients undergoing transfemoral (TF) TAVI. Methods: We conducted an observational study using a retrospective chart review of patients treated between 2011 and 2013 to identify patient characteristics, peri-procedure details, in-hospital outcomes and elimination-related complications in patients who did or did not receive a peri-procedure indwelling catheter. Descriptive analyses were used to report differences between the groups; we conducted a regression analysis to explore the relationship between the practice of urinary catheterization and total procedure time. Results: Of the 408 patients who underwent TF TAVR, 188 (46.1%) received a peri-procedure indwelling urinary catheter and 220 (53.9%) did not. There was no difference in in-hospital mortality (2.2%), disabling stroke (0.5%), or other major cardiac adverse events. The avoidance of a urinary catheter resulted in significantly lower rates of urinary tract infection requiring a new antibiotic regimen (1.4% versus 6.1%, p = 0.014), haematuria documented by medicine or nursing (3.7% versus 17.6%, p = 0.001), and the need for continuous bladder irrigation (2.7% versus 0%, p = 0.027). Conclusion: The avoidance of a urinary catheter may contribute to improved outcomes in patients undergoing TAVI. The intervention should be further evaluated within the broader study of minimalist TAVI.